2011
DOI: 10.1111/j.1759-6831.2010.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and phylogeography of a relict tree fern, Sphaeropteris brunoniana (Cyatheaceae) from China and Laos inferred from cpDNA sequence variations: Implications for conservation

Abstract: In this study, we analyzed the genetic structure and phylogeography of Sphaeropteris brunoniana from China and Laos. Combining cpDNA trnL‐trnF and atpB‐rbcL sequence variations, five haplotypes were identified from the 10 investigated populations. Moderate haplotype diversity (h= 0.66580) and low nucleotide diversity (π= 0.23 × 10−3) were detected. The S. brunoniana in Yunnan region had much higher genetic diversity (h= 0.60195, π= 0.35 × 10−3) than that of Hainan–Laos (h= 0.00000, π= 0.00). A high level of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…as refugia during the Quaternary glacial periods, and then recolonized QTP and its surrounding regions during the interglacial phases or at the end of the Last Glacial Maximum (LGM) [35,9095]. While the other hypothesis suggested some species may have also survived at QTP and its surrounding regions in situ through the Quaternary [96,97]. Previous studies in NW China showed species survival in East Tianshan Mountains [22] and Ili (Yili) Valley [33] during the Quaternary.…”
Section: Discussionmentioning
confidence: 99%
“…as refugia during the Quaternary glacial periods, and then recolonized QTP and its surrounding regions during the interglacial phases or at the end of the Last Glacial Maximum (LGM) [35,9095]. While the other hypothesis suggested some species may have also survived at QTP and its surrounding regions in situ through the Quaternary [96,97]. Previous studies in NW China showed species survival in East Tianshan Mountains [22] and Ili (Yili) Valley [33] during the Quaternary.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple refugia may have remained for these species, at least during the LGM (e.g., Wang et al, 2009b; Jia et al, 2011, 2012; Zhang et al, 2012). In fact, the multiple refugia of SW China remained for the studied species (e.g., Gao et al, 2007; Yuan et al, 2008; Wang & Guan, 2011). In western China, deserts seemed to have promoted the allopatric divergences of the studied species and these diverged populations should have survived in the different refugia during the LGM (e.g., Guo et al, 2010; Wang et al, 2011c; An et al, 2012; Li et al, 2012b, 2012d; Zhang & Zhang, 2012).…”
Section: Phylogeographic Patterns Of Plants In Chinamentioning
confidence: 99%
“…Most parts of China are deemed to have been free of an extensive ice sheet (Shi et al, 2006); however, species still experienced glacial‐time retreats and interglacial recolonizations in response to cold–warm climatic cycles. During glacial episodes, separate refugia during glacial advances are hypothesized to have triggered lineage divergence in many species (Gao et al, 2007; Wang et al, 2009a; Guo et al, 2010; Tang et al, 2010; Li et al, 2011; Wang & Guan, 2011). Likewise, evidence from low levels of genetic diversity indicate that demographic expansion, resulting in the founder effect, has frequently occurred following the onset of interglacial warming (Cun & Wang, 2010; Zhang et al, 2010).…”
mentioning
confidence: 99%